2021
DOI: 10.1186/s12986-021-00549-0
|View full text |Cite
|
Sign up to set email alerts
|

Lotus leaf extract inhibits ER− breast cancer cell migration and metastasis

Abstract: Background Patients with estrogen receptor negative (ER−) breast cancer have poor prognosis due to high rates of metastasis. However, there is no effective treatment and drugs for ER− breast cancer metastasis. Our purpose of this study was to evaluate the effect of lotus leaf alcohol extract (LAE) on the cell migration and metastasis of ER− breast cancer. Methods The anti-migratory effect of LAE were analyzed in ER− breast cancer cells including SK… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Since the composition of extracts is different, the most efficient inhibited concentration of CSE on SMMC‐7721 cells was higher than other plant extracts [20,31] . Similarly, it has been reported that the highest inhibited concentrations of lotus leaf and Brassica rapa L. extracts on ER– breast cancer cells and lung adenocarcinoma cells were 250 μg/mL and 300 μg/mL, respectively [32–33] . The toxicity of extracts on normal cells was the key factor for their application, our previous research suggested that CSE had certain inhibitory effects on SMMC‐7721, Hep3b, HepG2, HeLa, and L02 for 24 h. Among them, the inhibitory effect on SMMC‐7721 and HeLa was the strongest, IC50 values were 0.43 g/L and 0.37 g/L, while the cytotoxicity to normal cells L02 was 2.87 g/L and have low toxicity [24] .…”
Section: Discussionmentioning
confidence: 93%
“…Since the composition of extracts is different, the most efficient inhibited concentration of CSE on SMMC‐7721 cells was higher than other plant extracts [20,31] . Similarly, it has been reported that the highest inhibited concentrations of lotus leaf and Brassica rapa L. extracts on ER– breast cancer cells and lung adenocarcinoma cells were 250 μg/mL and 300 μg/mL, respectively [32–33] . The toxicity of extracts on normal cells was the key factor for their application, our previous research suggested that CSE had certain inhibitory effects on SMMC‐7721, Hep3b, HepG2, HeLa, and L02 for 24 h. Among them, the inhibitory effect on SMMC‐7721 and HeLa was the strongest, IC50 values were 0.43 g/L and 0.37 g/L, while the cytotoxicity to normal cells L02 was 2.87 g/L and have low toxicity [24] .…”
Section: Discussionmentioning
confidence: 93%
“…Nuciferine (Nuci), an aporphine alkaloid isolated from Nelumbo nucifera Gaertn, has been widely used in both daily diet and traditional Chinese medicine [ 1 ]. It has been clinically used for hemorrhage and postpartum blood halo according to the Chinese Pharmacopoeia and also reported with the properties of anti-obesity, anti-oxidation, anti-hyperglycemia, anti-bacteria, anti-tumor, and anti-cerebral ischemia in experimental models [ 2 ].…”
Section: Introductionmentioning
confidence: 99%